TiO2–Alginate–Chitosan-Based Composites for Skin Tissue Engineering Applications - Emma Bobu; Kata Saszet; Zsejke-Réka Tóth; Emőke Páll; Tamás Gyulavári; Lucian Baia; Klara Magyari; Monica Baia (Gels, 2024)
The UV-B component of sunlight damages the DNA in skin cells, which can lead to skin cancer and premature aging. Therefore, it is necessary to use creams that also contain UV-active substances. Many sunscreens contain titanium dioxide due to its capacity to absorb UV-B wavelengths. In the present study, titan dioxide was introduced in alginate and chitosan–alginate hydrogel composites that are often involved as scaffold compositions in tissue engineering applications. Alginate and chitosan were chosen due to their important role in skin regeneration and skin protection. The composites were cross-linked with calcium ions and investigated using FT-IR, Raman, and UV–Vis spectroscopy. The stability of the obtained samples under solar irradiation for skin protection and regeneration was analyzed. Then, the hydrogel composites were assayed in vitro by immersing them in simulated body fluid and exposing them to solar simulator radiation for 10 min. The samples were found to be stable under solar light, and a thin apatite layer covered the surface of the sample with the two biopolymers and titanium dioxide. The in vitro cell viability assay suggested that the anatase phase in alginate and chitosan–alginate hydrogel composites have a positive impact.